REGRESSION MODELS FOR DETERMINING THE OPERATING COSTS OF FORESTRY MILLING MACHINES FOR COMPLETE SOIL PREPARATION FOR REFORESTATION OF POPLAR CLEARINGS - Marinov, Konstantin; Peev, Dimitar (Innovation in Woodworking Industry and Engineering design, 2026)
This paper presents the results of an experimental study conducted with a self-propelled milling unit PT-400 with a multifunctional forestry milling machine FAE 300/S-225 for complete soil preparation for reforestation of poplar clearings. Regression models were developed to determine the relative fuel consumption and time consumption for complete soil preparation of poplar clearings. Based on the obtained results, the influence of the speed parameters of the forestry cutters and the working conditions in the fellings on the size of the operating costs was determined. Of all the factors that express the conditions of work, the diameter and density of the stumps have the greatest weight and dominance on the cost indicators. The amount of shredded shoots, bushes and wood waste ranks third, and the mechanical composition of the soil has the least influence. To mitigate the impact of more severe working conditions, it is best to use the cutter’s "rotational frequency" factor. Regardless of the type of technological operation performed, lower operating costs are obtained at a higher frequency of rotation of the cutter. Given that this factor can be managed within wider limits, it is recommended that forestry cutters for shredding stumps and roots and mulching wood waste, shoots and bushes, operate at a higher frequency of rotation of the rotor – over 500 min-1.